Productivity analysis in oil palm plantations using the objective matrix method: case study PT. Dharma Satya Nusantara Tbk. - Mas'ud, Mufid; Pawitra, Theresia Amelia; Fathimahhayati, Lina Dianati (Universitas Mercu Buana, 2024)
PT. DSN Group Tbk, a company operating in palm oil plantations, wood products, and renewable energy, manages a 112,450-hectare palm oil plantation, including 84,566 hectares of core plantation and 27,884 hectares of plasma plantation. This research aims to identify and measure productivity criteria in the palm oil plantation and suggest improvements. The Objective Matrix (OMAX) method was used to evaluate productivity, revealing that the highest productivity index in 2021 was 136.67% in March, while the lowest was -36.67% in September. In 2022, the highest index was 101.67% in August, with the lowest at -35% in May. The Fishbone Diagram identified causes for productivity declines: in 2021, human-related issues were the primary factor, while in 2022, failure to meet production targets was the main concern. Proposed improvements include redesigning harvesting tools to reduce worker fatigue, remapping the plantation, conducting regular checks for fruit quality, maintaining farm equipment, and training workers to prevent over-fertilization.